The Assessment of Marine Tourism Destination in North Seribu Islands, DKI Jakarta with Recreation Opportunity Spectrum Approach - Anang Sutono; Rinie Octaviany Hasan; Beta Budi Setyorini; Dewa Putu Oka Prasiasa; Shaharuddin Tahir; Indra Kusumawardhana; Rudy P. Siahaan; Fajar Aditya Nugroho (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
The North Seribu Islands isn’t only become a favorite marine tourism destination for domestic and foreign tourists, but have also been able to keep maintain stability and natural sustainability. Recreation Opportunity Spectrum (ROS) was used to assess the North Seribu Islands region as a marine tourism destination. Using the qualitative analysis and Point Rating Scale methods, it was found that the eleven islands of North Seribu Islands being studied in this research have been classified into three classes according to the Recreation Opportunity Spectrum. Among them, there are 4 islands classified as accessible, such as Pramuka Island, Panggang Island, Harapan Island, and Kelapa Dua Island. The main products produced by each class are expected to meet varying levels of tourist expectations (output in the form of psychological) because the tastes of each individual in outdoor recreation are different.